Different acyl-CoA:diacylglycerol acyltransferases vary widely in function, and a targeted amino acid substitution enhances oil accumulation. (4th March 2022) - Hatanaka, Tomoko; Tomita, Yoshiki; Matsuoka, Daisuke; Sasayama, Daisuke; Fukayama, Hiroshi; Azuma, Tetsushi; Soltani Gishini, Mohammad Fazel; Hildebrand, David
Abstract : Seven DGAT1 genes were tested for their effects on triacylglycerol accumulation in Arabidopsis and yeast. They were divided into high and low function, and site-directed mutagenesis enhanced their function in yeast. Abstract: Triacylglycerols (TAGs) are the major component of plant storage lipids such as oils. Acyl-CoA:diacylglycerol acyltransferase (DGAT) catalyzes the final step of the Kennedy pathway, and is mainly responsible for plant oil accumulation. We previously found that the activity of Vernonia DGAT1 was distinctively higher than that of Arabidopsis and soybean DGAT1 in a yeast microsome assay. In this study, the DGAT1 cDNAs of Arabidopsis, Vernonia, soybean, and castor bean were introduced into Arabidopsis. All Vernonia DGAT1 -expressing lines showed a significantly higher oil content (49% mean increase compared with the wild-type) followed by soybean and castor bean. Most Arabidopsis DGAT1 -overexpressing lines did not show a significant increase. In addition to these four DGAT1 genes, sunflower, Jatropha, and sesame DGAT1 genes were introduced into a TAG biosynthesis-defective yeast mutant. In the yeast expression culture, DGAT1s from Arabidopsis, castor bean, and soybean only slightly increased the TAG content; however, DGAT1s from Vernonia, sunflower, Jatropha, and sesame increased TAG content >10-fold more than the former three DGAT1s. Three amino acid residues were characteristically common in the latter four DGAT1s. Using soybean DGAT1, these amino acid substitutions were created by site-directed mutagenesis and substantially increased the TAG content.